Exploring Social and Religious Dimensions: A Qualitative Analysis of Computer Literacy and Motivational Empowerment among Maritime Cadets in an International Programme - Marudut Bernadtua Simanjuntak (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This study delves into the intricate interplay of social, religious, and academic facets within the Maritime Institute Jakarta (STIP Jakarta), specifically focusing on Semester 1 cadets enrolled in the international programme. The research centres on the competencies of 200 randomly selected cadets, examining their proficiency in computer literacy while scrutinizing the influence of social and religious perspectives on their pursuit of an international maritime education. This investigation aligns with the International Maritime Organization's (IMO) Standards of Training, Certification, and Watchkeeping (STCW) framework, emphasising the paramount importance of English communication skills for future global officers. Maritime Institute Jakarta (STIP Jakarta), renowned for producing a substantial number of qualified seamen, deck officers, and engine officers, offers applied bachelor's degrees in Nautical, Technical, and Port and Shipping Management majors. Cadets, hailing from diverse regions across Indonesia, incorporate Bahasa Indonesia and their traditional languages into their daily lives. However, the demand for international and global proficiency necessitates fluency in English communication. The research methodology adopts a qualitative approach with a focus on descriptive analysis. By investigating the social and motivational empowerment aspects, the study aims to uncover the intricate dynamics that influence the cadets' journey. Attention is given to the prayers and expectations of parents, reflecting on the cadets' plans and aspirations to become exceptional seafarers. The qualitative lens employed in this study allows for a nuanced understanding of the cadets' experiences, exploring the multifaceted dimensions of their educational journey. This research not only contributes to the understanding of computer literacy among maritime cadets but also sheds light on the socio-religious context that shapes their educational pursuits. The findings are anticipated to inform educational policies, curriculum development, and support systems tailored to the unique needs of maritime cadets in an international setting.